IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION IN BUILDING STUDENTS' RELIGIOUS VALUES IN SMP MUHAMMADIYAH 1 PURWOKERTO - Muh Hizbul Muflihin (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to determine the process of implementing Islamic religious education in building religious values in the school environment at SMP Muhamadiyah 1 Purwokerto and intracurricular learning conducted by Islamic religious education teachers at SMP Muhammadiyah 1 Purwokerto. The research method uses a qualitative descriptive approach. The data source was selected purposively and was snowball sampling. Data collection techniques were carried out by observation, interview and documentation methods. Meanwhile, data analysis was done by descriptive analysis. The results of this study have shown that the implementation of Islamic religious education in building religious values in schools. It has been implemented in daily activities such as getting used to greetings, shaking hands, being polite in speaking, polite in behaving, and respecting teachers and fellow friends. Carry out religious curriculum programs, such as holding Al-Quran Reading, Dhuha Prayers in congregation, Dhuhur Prayers in congregation, Developing talents such as speeches, lectures, Islamic studies, Memorizing Al-Qur'an, Discipline. Intracurricular learning of Islamic religious education at SMP Muhammadiyah 1 Purwokerto is carried out systematically using the 2011 curriculum. Student-centered intracurricular learning with conceptual and illustrative material aspects as well as contextual examples. Conducting assessment by attitude and control through attitude and developments in religious practice.